Expansion Design of Interferometric Aperture Synthesis Arrays Based on Multi-Objective Optimization - Dong Zhu; Fei Hu; Xiaohui Peng (IEEE Access, 2019)
This paper presents a study on expansion design of thinned arrays in interferometric aperture synthesis radiometers. The design problem deals with how to properly employ a limited number of antenna elements around a fixed array to fulfill performance requirements of interest, such as angular resolution, peak sidelobe level, and array redundancy. These factors of merit are grouped and discussed within the framework of multi-objective design. Three state-of-the-art optimizers based on multi-objective particle swarm optimization, non-dominated sorting genetic algorithm II, and non-dominated neighbor immune algorithm are implemented for specific design examples. A comparative analysis is performed to point out the features and performances of the above-mentioned search methods.